Back in the Trenches - Corbett, Glenn J. (The Biblical archaeology review, 2023)
Over the past year, biblical archaeology, like many fields and professions, has thankfully seen a gradual return to the familiar rhythms of pre-pandemic life. Scholars are again meeting at conferences to present their latest findings, BAR readers and archaeology enthusiasts are once again traveling to BAS seminars and taking part in overseas study tours, […]